Neutralization of human immunodeficiency virus type 1 by antibody to gp120 is determined primarily by occupancy of sites on the virion irrespective of epitope specificity. - Parren, P; Mondor, I; Naniche, D; Ditzel, H; Klasse, P; Burton, DR; Sattentau, Q (1998)
We investigated the relative importance of binding site occupancy and epitope specificity in antibody neutralization of human immunodeficiency virus (HIV) type 1 (HIV-1). The neutralization of a T-cell-line-adapted HIV-1 isolate (MN) was analyzed with a number of monovalent recombinant Fab fragments (Fabs) and monoclonal antibodies with a range of specificities covering all confirmed gp120-specific neutralization epitopes. Binding of Fabs to recombinant monomeric gp120 was determined by surface plasmon resonance, and binding of Fabs and whole antibodies to functional oligomeric gp120 was determined by indirect immunofluorescence and flow cytometry on HIV-infected cells. An excellent correlation between neutralization and oligomeric gp120 binding was observed, and a lack of correlation with monomeric gp120 binding was confirmed. A similar degree of correlation was observed between oligomeric gp120 binding and neutralization with a T-cell-line-adapted HIV-1 molecular clone (Hx10). The ratios of oligomer binding/neutralization titer fell, in general, within a relatively narrow range for antibodies to different neutralization epitopes. These results suggest that the occupancy of binding sites on HIV-1 virions is the major factor in determining neutralization, irrespective of epitope specificity. Models to account for these observations are proposed.